Postoperative morphological changes over time of vascularized scapular bone used for mandibular reconstruction: A retrospective cohort study. Issue 9 (September 2021) - Mochizuki, Yumi; Marukawa, Eriko; Harada, Hiroyuki; Kinoshita, Naoya; Nakatani, Ryo; Oikawa, Yu; Hirai, Hideaki; Tomioka, Hirofumi; Yoda, Tetsuya; Nakamura, Shin; Kurabayashi, Tohru
Summary: Background: Currently, sequential morphological changes of vascularized scapular bone for mandibular reconstruction have remained unreported. Methods: We retrospectively analyzed 18 patients with defects on the lateral segment of the mandible who underwent postoperative computed tomography (CT) scanning at 1, 6, 12, and 24 months postoperatively. Using the cross-sectional coronal CT images during each assessment, we measured the height and thickness of the grafted scapular bone at points 10 and 30 mm away from the mesial segment and evaluated their differences over time. Then, the relationship between the morphological changes of the grafted scapular bone and the distance from the mesial bone segment, the number of occlusal supports on the contralateral side of the mandible, and the correlation of sex and age were evaluated. Results: The height of the grafted scapular bone decreased by approximately 11% and its thickness increased by 14% within 24 months postoperatively. The bone thickness increase was greater at point 30 mm from the mesial bone segment. Patients with two occlusal contacts (premolar and molar) on the contralateral side had a significantly higher rate of bone thickness increase. Furthermore, the graft morphology was not associated with age or sex. Conclusion: A vascularized scapular bone thickens over time, which depends on the distance from the mesial bone segment and the occlusal contact regions on the contralateral side of the mandible.